Prevention of Anemia in Adolescent Girls in Pangkalan Jati Village, Cinere, Depok - Mila Citrawati; Maria Selvester Thadeus; Tiwuk Susantiningsih; Yuni Setyaningsih (Abdimas Indonesian Journal, 2026)
Stunting remains a major public health issue that must be addressed today. Stunting represents a significant nutritional problem that affects social and economic life both within and across communities. There is clear evidence that stunted individuals have higher mortality rates and greater disease incidence. Contributing factors to stunting include inadequate nutritional intake during pregnancy, which leads to fetal growth restriction, marking the beginning of stunting. Stunting prevention education is essentially an activity or effort to convey messages to communities, groups, or individuals with the expectation that they will gain knowledge that can influence their attitudes and behaviors. The youth of the Al Muhajirin Mosque in Pangkalan Jati, Cinere, Depok, have limited knowledge regarding the dangers of anemia among adolescent girls and its link to stunting. The objective of this community service activity was to educate the youth members of Al Muhajirin Mosque about the dangers of anemia and the importance of iron supplementation to reduce the risk of stunting in children. Our finding that this activity can increase adolescents’ understanding of anemia and stunting, thereby contributing to the reduction of anemia and stunting rates in Pangkalan Jati, Cinere, Depok.